The efficiency of nuclear burning during thermonuclear (Type I) bursts as a function of accretion rate. Issue 2 (22nd September 2020) - Cavecchi, Y; Galloway, D K; Goodwin, A J; Johnston, Z; Heger, A
ABSTRACT: We measured the thermonuclear burning efficiency as a function of accretion rate for the Type I X-ray bursts of five low-mass X-ray binary systems. We chose sources with measured neutron star spins and a substantial population of bursts from a large observational sample. The general trend for the burst rate is qualitatively the same for all sources; the burst rate first increases with the accretion rate up to a maximum, above which the burst rate declines, despite the increasing accretion rate. At higher accretion rates, when the burst rate decreases, the α-value (the ratio of accretion energy and burst energy) increases by up to a factor of 10 above that in the rising burst rate regime. These observations are contrary to the predictions of 1D numerical models, but can be explained as the consequence of a zone of stable burning on the neutron star surface, which expands with increasing accretion rate. The stable burning also 'pollutes' the unstable burning layer with ashes, contributing to the change in burst properties measured in the falling burst rate regime. We find that the mass accretion rate at which the burst rate begins to decrease is anticorrelated with the spin of the neutron star. We conclude that the neutron star spin is a key factor, moderating the nuclear burning stability, via the local accretion rate and fuel composition over the star.